(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
The cataract is the leading cause of blindness and affecting nearly 22 million Americans aged 40 and older. Cataract screening is a process usually carries out by an ophthalmologist using specialize equipment. The hurdles that we are facing today to screen for cataract include the availability of medical practitioner and proper equipment, especially in the rural area. Other problems include the cost and time involved to do eye examination from the medical practitioner. In this paper, we aim to research on an alternate cataract screening solution using a flash-enabled smartphone without any external attachments. The solution should be made usable by general public. The research is divided into three different phases. The first phase aims to understand how medical practitioner performs cataract screening using red reflex and attempts to replicate it using mobile application. The second phase involves collecting data to obtain the appropriate parameters that allow replication of red reflex using mobile application. The third phase of this research intends to replicate the Ophthalmologist diagnosis using Artificial intelligent built into the mobile application. This paper presents the work performed and the obtained outcome from the first and second phases.